The Code of the City of Atlanta 164 (William T. Newman ed., 1879) - (:unkn) unknown (My University, 1879)
Ch. 42-Powder, § 461: In order to receive a license, all petitioners shall give the names of three neighbors who approve of the sale of gunpowder. Petitioners shall pay a one thousand dollar bond and security.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER